SOCİO-POLİTİCAL CRİTİQUE İN GOGOL'S "DEAD SOULS": UNVEİLİNG THE MALAİSE OF FEUDAL RUSSİA - Zeynab Mammadova; Salman Aliyev (Theoretical Hypotheses and Empirical Results, 2023)
This article delves into Nikolai Gogol's seminal work, "Dead Souls," dissecting its profound socio-political critique that meticulously unveils the intricate maladies plaguing feudal Russia. Gogol, a literary maestro, employs his discerning gaze to scrutinize and castigate each facet of the political and legal landscape, rendering a compelling narrative that transcends the conventional bounds of realism. Within the feudal tapestry of the narrative, the disillusionment of the populace with the state apparatus emerges as a poignant theme. Citizens, bereft of hope, resort to fraudulent practices, illustrating the pervasive corruption that permeates society. Bureaucrats, disenchanted with the inefficacy of the state, succumb to the allure of bribery, further entrenching systemic corruption. Legal practitioners exploit existing loopholes, emphasizing the erosion of ethical considerations in the pursuit of personal gain. The article explores how this materialistic ethos breeds a society characterized by deceit and indulgence, submerging any altruistic principles in a sea of pleasure-seeking endeavors. Furthermore, Gogol's narrative exposes the dehumanizing treatment of slaves, emblematic of feudalistic practices. Their plight, overlooked and callously disregarded, serves as a stark commentary on the moral bankruptcy inherent in such societal structures. The erosion of educational values, manifested through a stifling of dissent and the cultivation of conformity, further accentuates the multifaceted critique embedded in Gogol's work. "Dead Souls," marked by satire and irony, emerges not merely as a realistic novel but as a transcendent exploration of allegorical and symbolic dimensions. Its universal resonance has propelled it to global acclaim, standing as a testament to Gogol's ability to illuminate the societal flaws of his time with unparalleled depth and insight.